The Effect of Sustainability Report and Good Corporate Governance on Firm Value in Manufacturing Companies Listed on the Indonesian Sharia Stock Index (ISSI) - Salwa Dzahabiyyah; Mismiwati; Titin Hartini; Rika Lidyah; Peny Cahaya Azwari (CV. Doki Course and Training, 2025)
This study aims to determine the effect of sustainability reports and boards of commissioners on company value in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) from 2021 to 2023. A quantitative method was used in this study. The secondary data used were annual financial reports and company sustainability reports obtained from official websites and www.idx.co.id. The sampling technique used was purposive sampling. This study used panel data regression analysis as its analysis method. The findings show that sustainability reports have a positive and significant effect on company value, while the board of commissioners (GCG) has a negative and significant effect on company value.